Pembuatan Website Company Profile sebagai Media Publikasi Menggunakan CMS Wordpress di PT Global Putra Ventura Sejahtera Kota Surabaya - Moh. Choirul Abidin; Joni Dwi Pribadi; Maskur (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Global Putra Ventura Sejahtera is a B2B company specializing in the provision of installation services, procurement of goods, and telecommunications infrastructure in Indonesia. Currently, PT Global Putra Ventura Sejahtera only uses personal Email and Whatsapp as their digital publication platforms. As the company continues to grow, these two platforms have become less effective in supporting the company's publication activities since they cannot reach potential clients outside the company's network, and exacerbate them to establish their brand and disseminate information. This study aims to create a company profile website using the WordPress CMS as an effective publication platform that can be accessed by everyone on the internet. The research method used was action research involving seven respondents, consisting of one computer expert, one website UI/UX expert, two marketing experts, one company public relations staff member, one company administrative staff member, and one company director. Data was collected through observation, interviews, questionnaires, and documentation. Data analysis was conducted using the WebQual method with three indicators, Usability Quality, Information Quality, and Interaction Quality, to measure the website's quality as a publication medium. The research results show that in the first cycle, the website achieved a WebQual score of 88.3%, which falls into the “very good” category. After improvements based on feedback from respondents were made, there was an increase in results, with the WebQual score improving to 94.57%, and no significant suggestions were made. The website can be considered “very good” in terms of the information displayed, usability, and interaction with users. It can be concluded that the company profile website created using WordPress CMS demonstrates excellent information quality and website quality, making it suitable for use as a company publication medium.